Delegation of the North Caucasus to France (1919–1920). - Irina L. Babich (Кавказология)
This article is devoted to the history of the delegation sent by the Mountain Republic to France, to an international conference (1919). The delegation’s purpose is the obtainment of international recognition as an independent state. This study was conducted based on archival documents discovered by us in France. This paper throughly analyzes the name of the delegation, its composition, and activities in Constantinople and Paris during the 1919-1920’s. The role of A.M. Chermoyev and G. Bammat is revealed, and the struggle of the new North Caucasian leaders formed in emigration with the delegation of the Mountain Republic is studied. The author believes that the end of the delegation’s activity can be dated back to 1930. It has been determined that it played a significant role in shaping the socio-political ideology of the North Caucasian community in France, reinforcing the position of North Caucasians in the region's political sphere, and creating a new generation of North Caucasian politicians.